Multiple Fetal Nutritional Patterns Before Parturition in Viviparous Fish Sebastes schlegelii (Hilgendorf, 1880) - Tengfei, Du; Yongshuang, Xiao; Haixia, Zhao; Li, Zhou; Qinghua, Liu; Xueying, Wang; Jun, Li; Shihong, Xu; Yanfeng, Wang; Jiachen, Yu; Lele, Wu; Yunong, Wang; et al. (Frontiers in Marine Science, 2021)
Sebastes schlegelii is a commercially important fish with a special viviparous reproductive system that is cultured in near-shore seawater net cages in East Asia. In the gonadal development of the species, the gonad of males mature before those of females, which mature after mating. Mating in male/female fishes occurs in October of each year. Then, females undergoing oocyte maturation complete fertilization using stored sperm in March of the following year. The pregnancy is completed when larvae are produced in the ovary. It has been reported that embryonic nutrient supply originates entirely from the female viviparous reproductive systems. However, until now, the nutritional patterns and the processes of nutrient provision in S. schlegelii before parturition have not been clear. The goal of this research was to study the embryos, larvae and juveniles of S. schlegelii during pregnancy. Anatomical observations, light microscopy and scanning electron microscopy were used to study the developmental characteristics of early embryos and larvae and the connecting structures between the mother and the foetus. The results showed the following: (1) Placental-like structures were found during the process of embryonic development in S. schlegelii, and these placental-like structures proliferated after fertilization. (2) The embryos of S. schlegelii were encased by a saclike structure composed of blood vessels, connective tissue and surface epithelial cells. The vessels near the embryo existed in the thecal layer. Vascularized proliferation was detected following embryonic development. (3) Starting in the gastrula stage, connections between the embryo and surrounding cells loosened, and ovarian fluid became abundant. In addition, a large number of small holes and cristae were observed on the surface of the embryo. We speculate that embryos may be able to absorb nutrients from the ovarian fluid. (4) Yolk was present throughout embryo development. (5) Two types of nutritional modes were observed, lecithotrophic and matrotrophic during embryonic development. Three forms of placental analogues may exist in S. schlegelii: 1) external epithelial absorptive surfaces; 2) trophonemata, with modifications of the ovarian epithelia for absorbing the histotroph; and 3) a follicular pseudoplacenta, with close apposition between follicle cells and embryonic absorptive epithelia.